Предмет: Алгебра,
автор: sencalcapimi
![\sqrt{12 - x } = - x \sqrt{12 - x } = - x](https://tex.z-dn.net/?f=+%5Csqrt%7B12+-+x+%7D++%3D++-+x)
Ответы
Автор ответа:
0
Ответ:
x₁ = - 4 ; x₂ = 3 .
Объяснение:
√( 12 - x ) = - x
( √( 12 - x ) )²=(-x)²
12 - x = x²
x² + x - 12 = 0
D = 1 + 48 = 49 = 7²
x₁ = ( - 1 - 7 ) / 2 = - 8 / 2 = - 4
x₂ = ( - 1 + 7 ) / 2 = 6 / 2 = 3
Похожие вопросы
Предмет: Қазақ тiлi,
автор: martyushovan
Предмет: Русский язык,
автор: andrey2288
Предмет: Биология,
автор: таня11233
Предмет: Математика,
автор: peterbayroshoxq5ei